Reading Comprehension Activities in the Ugandan English as a Foreign Language Classroom - Rugyema, Rodney (East African Journal of Education Studies, 2024)
The study examines the reading comprehension activities in the Ugandan English as a Foreign Language (EFL) classroom. It particularly analyses the activities that the learners of EFL participate in as part of their reading comprehension lessons. The study focusses on EFL learners from countries such as Congo, Eritrea, South Sudan, and Ethiopia, among others studying in Ugandan adult language schools. The specific objectives of the study were to identify the reading comprehension activities in the Ugandan EFL classroom and to establish the learners’ response to the reading comprehension activities used in the EFL class. Drawing on the transactional theory, the study analyses the reading comprehension activities and the learners’ response to them. The findings indicate that the most profound activities in the classes were pre-reading activities. In their order of frequency, pre-reading activities were the most profound in the classes observed, followed by while-reading and the post-reading activities, which were the least used. In the classes where reading activities were used, they excited the majority of the EFL learners and they paid attention to the lesson. The learners’ response to the activities was diverse with the majority expressing interest in the activities as others chose not to participate at all. The study recommends the use of more reading comprehension activities especially at the while- and post-reading comprehension stages of the lessons which were lacking in most of the classes observed. It further recommends involving the learners and putting into consideration their views during the identification and selection of reading comprehension activities to ensure their maximum participation in the reading comprehension activities